Presidential Decree-Law No. 113 Of The Year 2015 Amending Some Provisions of Law No. 11 of the Year 2004 on Establishing The Family Insurance System Fund = قرار رئيس جمهورية مصر العربية بالقانون رقم 113 لسنة 2015 بتعديل بعض أحكام القانون رقم 11 لسنة 2004 بإنشاء نظام تأمين الأسرة - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic